2006
DOI: 10.1371/journal.ppat.0020001
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Specific Countermeasures against Ebola Virus Based on Antisense Phosphorodiamidate Morpholino Oligomers

Abstract: The filoviruses Marburg virus and Ebola virus (EBOV) quickly outpace host immune responses and cause hemorrhagic fever, resulting in case fatality rates as high as 90% in humans and nearly 100% in nonhuman primates. The development of an effective therapeutic for EBOV is a daunting public health challenge and is hampered by a paucity of knowledge regarding filovirus pathogenesis. This report describes a successful strategy for interfering with EBOV infection using antisense phosphorodiamidate morpholino oligom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
110
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(112 citation statements)
references
References 36 publications
(44 reference statements)
0
110
0
2
Order By: Relevance
“…The four treated animals that survived challenge experienced little to no viremia and had few, if any, of the clinical symptoms observed in the two controls. With a caveat that direct comparisons between studies performed in different laboratories are difficult, this is in contrast to the course of disease seen in survivors treated with other EBOV therapeutic candidates in advanced development (siRNA, PMOs, and VSV) in which surviving animals experience varying levels of morbidity (3)(4)(5). Further, MB-003 RAMP provided this level of protection out to 48 h p.i.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The four treated animals that survived challenge experienced little to no viremia and had few, if any, of the clinical symptoms observed in the two controls. With a caveat that direct comparisons between studies performed in different laboratories are difficult, this is in contrast to the course of disease seen in survivors treated with other EBOV therapeutic candidates in advanced development (siRNA, PMOs, and VSV) in which surviving animals experience varying levels of morbidity (3)(4)(5). Further, MB-003 RAMP provided this level of protection out to 48 h p.i.…”
Section: Discussionmentioning
confidence: 99%
“…Currently there are no licensed vaccines or treatments against EBOV infection. Candidate postexposure interventions in advanced development include siRNA and phosphorodiamidate morpholino oligomers (PMOs) antisense strategies, as well as postexposure immunization with a vesicular stomatitis virus (VSV)-based vaccine (3)(4)(5). All of these interventions have demonstrated reduced mortality in NHPs when delivered 0.5-1 h postinfection (p.i.…”
mentioning
confidence: 99%
“…Since filoviruses encode their own replication/transcription machinery, the components involved in replication/transcription; cis-acting elements on the genomes and VPs mediating replication/transcription, are ideal targets for antiviral strategies. Indeed, initial approaches to use viral genes and proteins involved in replication/transcription as targets for antiviral compounds were quite promising [59,63,[67][68][69][70]. Thus, a deeper understanding of the way in which filoviruses replicate and transcribe their genomes will lead to potential benefits in controlling filovirus infections.…”
Section: Future Perspectivementioning
confidence: 99%
“…Subsequent studies have demonstrated promise for treatment of ZEBOV infections with antisense oligonucleotides and small interfering RNAs (27,28). An effective vaccine would reduce inherent hazards in working with these viruses.…”
Section: Discussionmentioning
confidence: 99%